Contrast enhancement of carotid adventitial vasa vasorum as a biomarker of radiation-induced atherosclerosis. Issue 1 (July 2016) - Gujral, Dorothy M.; Cheung, Wing Keung; Shah, Benoy N.; Chahal, Navtej S.; Bhattacharyya, Sanjeev; Hooper, James; Senior, Roxy; Tang, Meng-Xing; Harrington, Kevin J.; Nutting, Christopher M.
Abstract: Purpose: Abnormal proliferation of adventitial vasa vasorum (vv) occurs early at sites of atherosclerosis and is thought to be an early biomarker of vascular damage. Contrast-enhanced ultrasound (CEUS) can detect this process. Its usefulness in irradiated arteries as a measure of accelerated atherosclerosis is unknown. This study investigates contrast intensity in carotid adventitia as an early marker of radiation-induced damage in head and neck cancer (HNC) patients. Materials/methods: Patients with HNC treated with a wedged-pair and matched neck technique or hemi-neck radiotherapy (RT) (unirradiated side as control) at least 2 years previously were included. Patients had been prescribed a dose of at least 50 Gy to the neck. CEUS was performed on both carotid arteries and a region of interest was selected in the adventitia of the far wall of both left and right distal common carotid arteries. Novel quantification software was used to compare the average intensity per pixel between irradiated and unirradiated arteries. Results: 48 patients (34 males) with median age of 59.2 years (interquartile range (IQR) 49.2–64.2) were included. The mean maximum point dose to the irradiated artery was 61.2 Gy (IQR 52.6–61.8) and 1.1 Gy (IQR 1.0–1.8 Gy) to the unirradiated side. The median interval from RT was 59.4 months (IQR 41–88.7). There was a significant difference in the mean (SD) contrast intensity per pixel on the irradiated side (1.1 (0.4)) versus 0.96 (0.34) on the unirradiated side ( p = 0.01). After attenuation correction, the difference in mean contrast intensity per pixel was still significant (1.4 (0.58) versus 1.2 (0.47) ( p = 0.02). Previous surgery or chemotherapy had no effect on the difference in contrast intensity between the 2 sides of the neck. Mean intensity per pixel did not correlate to traditional risk prediction models (carotid intima-medial thickness, QSTROKE score). Conclusions: Proliferation of vv is demonstrated by increased contrast intensity in irradiated carotid arteries. This may be a useful, independent biomarker of radiation-induced carotid atherosclerosis when used as a tool to quantify neovascularization.